Heart Rate Variability Synchronizes When Non-experts Vocalize Together - Ruiz-Blais, Sebastian; Orini, Michele; Chew, Elaine (Frontiers in Physiology, 2020)
Singing and chanting are ubiquitous across the World's cultures. It has been theorised that such practices are an adaptive advantage for humans because they facilitate bonding and cohesion between group members. Investigations into the effects of singing together have so far focused on the physiological effects, such as the synchronisation of heart rate variability (HRV), of experienced choir singers. Here, we study whether HRV synchronises for pairs of non-experts in different vocalising conditions. Using time-frequency coherence (TFC) analysis, we find that HRV becomes more coupled when people make long (>10 s) sounds synchronously, compared to short sounds (<1 s), and baseline measurements (p<0.01). Furthermore, we find that although most of the effect can be attributed to respiratory sinus arrhythmia, some HRV synchronisation persists when the effect of respiration is removed: long notes show higher partial TFC than baseline and breathing (p<0.05). In addition, we observe that, for most dyads, the frequency of the vocalisation onsets matches that of the peaks in the TFC spectra, even though these frequencies are above the typical range of 0.04-0.4 Hz. A clear correspondence between high HRV coupling and the subjective experience of "togetherness" was not found. These results suggest that since autonomic physiological entrainment is observed for non-expert singing, it may be exploited as part of interventions in music therapy or social prescription programmes for the general population.